Osservando i pipistrelli (Balthazar, 2022)
Thomas Nagel’s 1974 essay “What Is It Like to Be a Bat?”[1] is one of the most cited texts on the problem of consciousness, and its theses have been discussed and debated in many different fields, from philosophy of mind to animal cognition and animal ethics. Nagel’s argument, that it is ultimately impossible for us to know what it is like to be a bat for a bat given the extreme differences in sensory experience between humans and bats, has come under fire from very different and even opposed perspectives: if, on the one hand, science-oriented philosophers and scholars accused him of underestimating and ultimately curtailing the power of scientific inquiry, on the other researchers in the humanities and animal ethics indicted him of defeatism for dismissing the power of imagination in bridging the species gap. In what follows, I will present and contrast two such positions, the critique of Nagel by neurophilosopher[2] Kathleen Akins and a very different approach to bat lives through poetry, exemplified by two poems by Ted Hughes (1930-1998) and Les Murray (1938-2019). The goal of counterposing these two different ways of looking at bats is not only or not much that of suggesting a preferable approach to bats’ otherness (though this is also what I will do), but also of emphasizing the aesthetic dimension of our relationship with the animal other and the role it plays in our ethical decision-making. [1] T. Nagel, “What Is It Like to Be a Bat?”, in The Philosophical Review, vol. 83, n. 4, 1974, pp. 435-450.[2] Neurophilosophy is an interdisciplinary field at the intersection of philosophy and the neurosciences in which traditional philosophical problems about the nature of the mind are approached through current findings within the neurosciences.